Geology of Gunung Kandu Area, Gopeng with Emphasis on Rock Slope Stability - Mohd Roslan, Siti Nurfathi Athira (2016)
The analysis of slope stability is an important aspect of research in geotechnical engineering as it can reduce the risk and hazard due to landslides and rockfall. The internal factors which affect slope stability are changes in rock condition, erosion and alteration of rocks by physical and chemical weathering which can cause the soil and rock cohesion to decrease thus resulting in formation of fracture and weak planes. In limestone, chemical weathering also can influence many parts of the rock structure. Rapid infiltration of acidic rainwater may react with the minerals in rock and can reduce the rock cohesion of the rock hill, thus reducing its shear strength. The difference in stability could be due to different inclination of the sliding surface. The different orientation and spacing of discontinuity on plane with respect to the slopes face also can create different type of slope failures. The significance of this slope stability analysis project conducted at Gunung Kandu is their close proximity to roads and developed areas. Geological mapping of the area surrounding Gunung Kandu showed that Gunung Kandu is composed of white to light grey, medium grained limestone. The flat ground in the vicinity of Gunung Kandu is either alluvium or tailing sands which are left-overs from the tin mining industry. Detailed structure mapping and analyse of the poles of the geological structures at the eastern end of the hill indicated that three cliff faces are unstable and prone to sliding and wedge failure. For cliff face 1, the retaining net should be installed on the cliff face that has major fractures and is prone to slope failure while for cliff faces 2 and 3, the best mitigative measure to prevent any fatalities is to keep the distance of buildings away from the hill by at least two 2 times the height of the first cliff face observed.